THE INFLUENCE OF HEAD OF WARD’S LEADERSHIP STYLE WITH NURSE’S JOB SATISFACTION (CASE STUDY AT JASA KARTINI HOSPITAL TASIKMALAYA) - Ardhiansyah Ramdhani; Marchaban Marchaban; Sumarni Sumarni (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Nurses are dominant health staffs in Jasa Kartini Hospital. The activities of nurses illustrate hospital’s image.Nurse performance influence by leadership of head of ward. Progressively according to leadership style appliedby head of ward will have an effect with the growing of nurse’s job satisfaction. There was problems that found atJasa Kartini Hospital related to nursing care service, there was complaint from patients and their family.This studyaimed to identify head of ward’s situational leadership style, to know nurse’s job satisfaction because of head of ward leadership style, and to know the correlation between head of ward leadership style with nurse’s job satisfaction.This research used the observation technique. The study was included into non experimental research. Research’sinstruments used leadership style questionnaire and job satisfaction questionnaire. The subject of this research was145 nurses of Jasa Kartini Hospital Tasikmalaya. The data were analyzed using multiple regression analysis .The result of the study showed that head of ward’s leadership style in Jasa Kartini Hospital was directiveleadership. The directive leadership,consultative leadership and participative leadership head of ward has positive effect toward the nurse’s job satisfaction.There was significant influence between head of ward’s leadership style withnurse’s job satisfaction that was 19%. Keywords: leadership style, job satisfaction